Voices of social dislocation, lost work and economic restructuring: Narratives from marginalised localities in the 'New Scotland'. (February 2020) - Clark, Andy; Gibbs, Ewan
Political discourse in contemporary Scotland increasingly revolves around the vision of a 'New Scotland', more prosperous and meritocratic than the rest of the United Kingdom. This has a convoluted relationship with Scotland's industrial past, and specifically the social dislocation experienced through deindustrialisation. This article analyses the deployment of this narrative within regeneration efforts in former industrial communities in Lanarkshire and Inverclyde, West Central Scotland, before counterpoising it with the reflections of former industrial workers and their families. It does so through an analysis of monuments to the industrial past, comparing those erected as part of regeneration schemes by local authorities with community efforts to commemorate past struggles and industrial disasters. This examination is accompanied by the use of oral history narratives to argue that there are two distinct understandings of the nature of place, space, struggles over social justice and communal identities within these localities, which lean heavily on the memory of the industrial past in contrasting ways.